Investigation on Noise-stability of the Optical Link by AM-VSB and - Panagiev, O. B. (Elektronika ir Elektrotechnika, 2009)
The influence of analogue AM-VSB signals on the transmission of digital signals such as M-ary quadrature amplitude modulation (QAM) over an optical fiber is analyzed. Up to the 450-500 MHz is spectrum for AM-VSB signals, while for M-QAM signals he is up to 862-1000 MHz. In these networks with jointly transmitting AM-VSB and M-QAM signals are used subcarrier multiplexing (SCM) and there are favorable conditions for laser “clipping”. In this case carrier-to-noise ratio of M-ary QAM can be significantly affected and BER rise. Ill. 8, bibl. 5 (in English; summaries in English, Russian and Lithuanian).